A new approach to investigating neural transposition challenges current insertion mapping strategies and provides an alternative explanation for differential transposon expression - Treiber, C (2016)
Prior work has suggested the provocative, and somewhat controversial idea, that transposable element mobilization introduces genomic heterogeneity in certain regions of the mammalian brain. Findings in the fruit fly suggested that this might be a conserved phenomenon. Perrat et al. (2013) reported that transposons are overexpressed in the αβ-Kenyon Cells (αβ-KCs) of the Drosophila mushroom bodies and whole genome sequencing suggested that de-novo insertions map to neural genes within these cells. In this study I revisited these topics and investigated what impact elevated transposon expression has on the heterogeneity of the genomes of αβ-KCs. Since post-mitotic transposon insertions occur in single DNA molecules, they are rare and difficult to detect, and are particularly hard to distinguish from experimental artefacts. I developed a new protocol to analyse transposon insertions in individual flies, instead of groups. This approach significantly increased the theoretical power to detect rare somatic insertion events, and it also enabled comparison to somatic genomes from cells isolated from the same animal. This advance allowed me to distinguish true somatic events from rare germline polymorphism in the fly population. Furthermore, the new analysis pipeline utilises longer overlapping sequencing reads, which permits the identification of the precise break points of transposon insertion events. I confirmed that some transposons are more highly expressed in αβ-KCs, but I did not find evidence that this increase correlates with an increased number of transposon insertions. In addition, I did not detect an increase in the number of transposon insertions with age, challenging the idea that damage accumulates with age. A set of in-silico simulation experiments revealed that the rate of putative somatic insertion events is comparable to the rate of presently unavoidable experimental artefacts. Lastly, my analyses suggest that elevated and cell-restricted expression of the LINE-like retrotransposon Ivk in αβ-KCs might result from its co-expression with the αβ-KC specific gene CG17684, within which a germline insertion of Ivk resides.